Calcium/Calmodulin Stimulates the Autophosphorylation of Elongation Factor 2 Kinase on Thr-348 and Ser-500 to Regulate its Activity and Calcium Dependence - Tavares, Clint D. J. (2012)
Eukaryotic elongation factor 2 kinase (eEF-2K) is an atypical protein kinase regulated by Ca(2+) and calmodulin (CaM). Its only known substrate is eukaryotic elongation factor 2 (eEF-2), whose phosphorylation by eEF-2K impedes global protein synthesis. To date, the mechanism of eEF-2K autophosphorylation has not been fully elucidated. To investigate the mechanism of autophosphorylation, human eEF-2K was co-expressed with λ-phosphatase, and purified from bacteria in a three-step protocol using a calmodulin-affinity column. Purified eEF-2K was induced to autophosphorylate by incubation with Ca(2+)/CaM in the presence of MgATP. Analyzing tryptic or chymotryptic peptides by mass spectrometry monitored the autophosphorylation over 0–180 minutes. The following five major autophosphorylation sites were identified, Thr-348, Thr-353, Ser-445, Ser-474 and Ser-500. In the presence of Ca(2+)/CaM, robust phosphorylation of Thr-348 occurs within seconds of adding MgATP. Mutagenesis studies suggest that phosphorylation of Thr-348 is required for substrate (eEF-2 or a peptide substrate) phosphorylation, but not self-phosphorylation. Phosphorylation of Ser-500 lags behind the phosphorylation of Thr-348, and is associated with calcium-independent activity of eEF-2K. Mutation of Ser-500 to Asp, but not Ala, renders eEF-2K calcium-independent. Surprisingly, this calcium-independent activity requires the presence of calmodulin.